A Literature-Based Update on Benincasa hispida (Thunb.) Cogn.: Traditional Uses, Nutraceutical, and Phytopharmacological Profiles. (10th December 2021) - Islam, Muhammad Torequl; Quispe, Cristina; El-Kersh, Dina M.; Shill, Manik Chandra; Bhardwaj, Kanchan; Bhardwaj, Prerna; Sharifi-Rad, Javad; Martorell, Miquel; Hossain, Rajib; Al-Harrasi, Ahmed; Al-Rawahi, Ahmed; Butnariu, Monica; et al.
Abstract : Benincasa hispida (Thunb.) Cogn. (Cucurbitaceae) is an annual climbing plant, native to Asia with multiple therapeutic uses in traditional medicine. This updated review is aimed at discussing the ethnopharmacological, phytochemical, pharmacological properties, and molecular mechanisms highlighted in preclinical experimental studies and toxicological safety to evaluate the therapeutic potential of this genus. The literature from PubMed, Google Scholar, Elsevier, Springer, Science Direct, and database was analyzed using the basic keyword " Benincasa hispida ." Other searching strategies, including online resources, books, and journals, were used. The taxonomy of the plant has been made by consulting "The Plant List". The results showed that B. hispida has been used in traditional medicine to treat neurological diseases, kidney disease, fever, and cough accompanied by thick mucus and to fight intestinal worms. The main bioactive compounds contained in Benincasa hispida have cytotoxic, anti-inflammatory, and anticancer properties. Further safety and efficacy investigations are needed to confirm these beneficial therapeutic effects and also future human clinical studies.